Hydration reactivity difference between dicalcium silicate and tricalcium silicate revealed from structural and Bader charge analysis - Qi, Chongchong; Xu, Xinhang; Chen, Qiusong (International journal of minerals, metallurgy and materials, 2022)
Cement hydration is the underlying mechanism for the strength development in cement-based materials. The structural and electronic properties of calcium silicates should be elucidated to reveal their difference in hydration reactivity. Here, we comprehensively compared β-C 2 S and M3-C 3 S and investigated their structural properties and Bader charge in the unit cell, during surface reconstruction and after single water adsorption via density functional theory. We identified different types of atoms in β-C 2 S and M3-C 3 S by considering the bonding characteristics and Bader charge. We then divided the atoms into the following groups: for β-C 2 S, Ca and O atoms divided into two and four groups, respectively; for M3-C 3 S, Ca, O, and Si atoms divided into four, four, and three groups, respectively. Results revealed that the valence electron distribution on the surface was more uniform than that on the unit cell, indicating that some atoms became more reactive after surface relaxation. During water adsorption, the electrons of β-C 2 S and M3-C 3 S were transferred from the surface to the adsorbed water molecules through position redistribution and bond formation/breaking. On this basis, we explained why β-C 2 S and M3-C 3 S had activity differences. A type of O atom with special bond characteristics (no O-Si bonds) and high reactivity existed in the unit cell of M3-C 3 S. Bader charge analysis showed that the reactivity of Ca and O atoms was generally higher in M3-C 3 S than in β-C 2 S. Ca/O atoms had average valence electron numbers of 6.437/7.550 in β-C 2 S and 6.481/7.537 in M3-C 3 S. Moreover, the number of electrons gained by water molecules in M3-C 3 S at the surface was higher than that in β-C 2 S. The average variations in the valence electrons of H 2 O on β-C 2 S and M3-C 3 S were 0.041 and 0.226, respectively. This study further explains the differences in the hydration reactivity of calcium silicates and would be also useful for the design of highly reactive and environmentally friendly cements.